The relationship between physical activity and plasma glucose level amongst Ellisras rural young adult males and females : Ellisras longitudinal study - Matshipi, Moloko; Monyeki, Kotsedi Daniel; Kemper, Han (International Journal of Environmental Research and Public Health, 2017)
Unhealthy lifestyle characteristics such as low physical activity (PA) and high plasma glucose levels (PGLs) may lead to the development of type 2 diabetes mellitus in adulthood. The aim of this study was to investigate (i) the level of physical activity; (ii) the prevalence of pre-diabetes and (iii) the relationship between PA and plasma glucose level in a rural Ellisras adult population aged 18 to 28 years. A total of 713 young adults (349 males and 364 females) who took part in the Ellisras Longitudinal Study participated in the study. Fasting plasma glucose levels were analysed using Accutrend glucose meters. Physical activity data was collected using a validated questionnaire. Linear regression was used to assess the relationship between PA and pre-diabetes. The prevalence of pre-diabetes was between 45.7% and 50.2% and that of physical inactivity was 67.3% and 71.0% for males and females, respectively. There was no signiﬁcant (p > 0.05) relationship between PA and pre-diabetes (beta = 1.016; 95% Conﬁdence Interval from 0.352 to 2.777). The health beneﬁts of PA increased with the increasing frequency, duration and intensity of exercise. The prevalence of pre-diabetes was found to be very high in this population. Our results suggest that greater physical activity is associated with low plasma glucose levels.
Journal article published in the International Journal of Environmental Research and Public Health 2017, 14, 198
Keywords: Physical activity; Plasma glucose levels; Prediabetes; Rural young adults; South Africa; Exercise; Prediabetic state; Adulthood; Blood sugar monitoring